Konsekuensi Hukum Terhadap Notaris yang Melakukan Tindak Pidana Pemalsuan Akta Kuasa Menjual (Studi Putusan No. 773/Pid.B/2021/PN.SMG) - Endah Wulandari; Alvi Syahrin; Rudy Haposan Siahaan (Jurnal Hukum Lex Generalis, 2025)
Notarial acts of falsifying authentic deeds harm the interests of parties and are subject to criminal punishment. This normative juridical research analyzes the procedure for making notarial power of attorney to sell deeds, notaries' legal responsibilities regarding falsification, and legal consequences based on Decision No. 773/Pid.B/2021/PN.Smg. Research findings indicate procedures must comply with the Notary Law and Notary Code of Ethics. Notaries may face administrative, civil, and criminal sanctions. In this decision, the notary was found guilty of falsifying 4 power of attorney to sell deeds and sentenced to 1 year 6 months imprisonment under Article 264 paragraph (1) jo Article 55 paragraph (1) sub-1 of the Criminal Code.